Revisiting the inter‐rater reliability of drug treatment assessments according to the STOPP/START criteria. Issue 2 (5th October 2022) - Parodi López, Naldy; Belfrage, Björn; Koldestam, Anders; Lönnbro, Johan; Svensson, Staffan A.; Wallerstedt, Susanna M.
Abstract : Aims: The aim of this study is to revisit the inter‐rater reliability of drug treatment assessments according to the Screening Tool of Older Persons' Prescriptions (STOPP)/Screening Tool to Alert to Right Treatment (START) criteria. Methods: Potentially inappropriate medications (PIMs) and potential prescribing omissions (PPOs) were independently identified by two physicians in two cohorts of older people (I: 200 hip fracture patients, median age 85 years, STOPP/START version 1; II: 302 primary care patients, median age 74 years, STOPP/START version 2). Kappa statistics were used to evaluate inter‐rater agreement. Results: In cohort I, a total of 782 PIMs/PPOs, related to 68 (78%) out of 87 criteria, were identified by at least one assessor, 500 (64%) of which were discordantly identified by the assessors, that is, by one assessor but not the other. For four STOPP criteria, all PIMs ( n  = 9) were concordantly identified. In cohort II, 955 PIMs/PPOs, related to 80 (70%) out of 114 criteria, were identified, 614 (64%) of which were discordantly identified. For three STOPP criteria, all PIMs ( n  = 3) were concordantly identified. For no START criterion, with ≥1 PPO identified, were all assessments concordant. The kappa value for PIM/PPO identification was 0.52 in both cohorts. In cohort II, the kappa was 0.37 when criteria regarding influenza and pneumococcal vaccines were excluded. Further analysis of discordantly identified PIMs/PPOs revealed methodological aspects of importance, including the data source used and criteria wording. Conclusions: When the STOPP/START criteria are applied in PIM/PPO research, reliability seems to be an issue not encountered in previous reliability studies. Abstract : When the STOPP/START criteria were applied by two physicians in two separate cohorts, the inter‐rater agreement was weak, in contrast to strong to almost perfect in prior reliability studies. Methodological aspects may explain the differences.